Shape visualization of dental inclination in Class I and bimaxillary protrusion malocclusions through Geometric Morphometric Analysis / Siti Balqish Oon ... [et al.] - Oon, Siti Balqish; Alias, Aspalilah; Abdul Ghani, Sarah Haniza; Norman, Noraina Hafizan (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Objectives: This study aimed to determine the shape of dental inclination between Class I malocclusion and bimaxillary protrusive Malay patients using geometric morphometric analysis obtained from lateral cephalometric radiographs. Materials and Methods: 128 Malay patients who met the inclusion criteria were recruited; of which 64 patients were in Class I malocclusion and another 64 patients in bimaxillary protrusion groups. Samples were in the age range of 18 to 40 years old, with a gender distribution of 41 males and 87 females. Pre-treatment orthodontic lateral cephalometric radiograph were traced and digitized. Thirteen landmarks of each radiograph were incorporated and converted into coordinates using TPSUtil software. The plots were then exported to MorphoJ Software for multiple Geometric Morphometric Analysis (GMA). Results: The results showed that there was a statistically significant difference (p<0.01) in shape of dental inclination between the groups. Discriminant analysis and cross validation of these groups demonstrated 98% accuracy in identifying two types of dental malocclusion. The grid graphs illustrated the shape of dental inclination of the bimaxillary protrusion group as being significantly more proclined when compared to Class I malocclusion. Conclusion: This study concludes that the dissimilarities in dental inclination are identifiable in Class I malocclusion and bimaxillary protrusion and the shape differences can be visualized using geometric morphometric analysis.